2016
DOI: 10.1038/ncomms12848
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-binding protein vigilin regulates VLDL secretion through modulation of Apob mRNA translation

Abstract: The liver is essential for the synthesis of plasma proteins and integration of lipid metabolism. While the role of transcriptional networks in these processes is increasingly understood, less is known about post-transcriptional control of gene expression by RNA-binding proteins (RBPs). Here, we show that the RBP vigilin is upregulated in livers of obese mice and in patients with fatty liver disease. By using in vivo, biochemical and genomic approaches, we demonstrate that vigilin controls very-low-density lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
66
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(77 citation statements)
references
References 68 publications
10
66
0
1
Order By: Relevance
“…It has been reported that knocking down hepatic Insr expression in WT mice reduced VLDL secretion (35). We thus speculated that the phenotype of reduced hepatic steatosis in HFD-Tg mice is related to active insulin signaling.…”
Section: Tudor-sn Promotes Hepatic Vldl Secretion In Hfd-tg Mice Alonmentioning
confidence: 85%
See 1 more Smart Citation
“…It has been reported that knocking down hepatic Insr expression in WT mice reduced VLDL secretion (35). We thus speculated that the phenotype of reduced hepatic steatosis in HFD-Tg mice is related to active insulin signaling.…”
Section: Tudor-sn Promotes Hepatic Vldl Secretion In Hfd-tg Mice Alonmentioning
confidence: 85%
“…6B). Given that insulin signaling benefits VLDL secretion (34,35), we sought to detect the capacity of VLDL secretion Figure 3. Identification of unregulated Tudor-SN-related genes involved in metabolism.…”
Section: Tudor-sn Promotes Hepatic Vldl Secretion In Hfd-tg Mice Alonmentioning
confidence: 99%
“…LLTP molecules are involved in extracellular transport of hydrophobic lipids and triglycerides (9, 10), binding nucleic acids (1517), and appear to be involved in the immune response (12–14). LLTPs, including apo B100, share a common ancestor (9) and therefore contain similar primary structures that impart similar functions.…”
Section: Discussionmentioning
confidence: 99%
“…LLTPs, including apo B100, share a common ancestor (9) and therefore contain similar primary structures that impart similar functions. For example, Vigilin contains 13 K-homology nucleic acid binding domains as compared to 11 similar sequences in apo B100, both molecules have been shown to bind RNA (25, 1517). VTG A2 also contains 10 K-homology RNA binding motifs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation